2021
DOI: 10.3390/jcm10163618
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones—An Underestimated Player in Dilated Cardiomyopathy?

Abstract: Dilated cardiomyopathy (DCM) is the most prevalent cardiomyopathy, typified by left ventricular dilation and systolic dysfunction. Many patients with DCM have altered thyroid status, especially lower levels of free triiodothyronine (T3) and elevated levels of thyroid-stimulating hormone. Moreover, growing evidence indicates that even subtle changes in thyroid status (especially low T3) are linked with a worse long-term prognosis and a higher risk of mortality. Notably, recent discoveries have shown that not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Thyroid hormones are known to mediate genomic and nongenomic effects on the heart, and recent studies have shown changes in gene expression associated with biosynthesis or diminished bioavailability of thyroid hormones at the tissue level among patients with dilated cardiomyopathy. 7 Cardiac dysfunction among patients with dilated cardiomypathy secondary to hypothyroidism can be reversed with thyroid hormone replacement therapy. 3,6 Although hypothyroidism alone is an uncommon cause of dilated cardiomyopathy, clinicians should perform thyroid function tests in patients with un explained dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are known to mediate genomic and nongenomic effects on the heart, and recent studies have shown changes in gene expression associated with biosynthesis or diminished bioavailability of thyroid hormones at the tissue level among patients with dilated cardiomyopathy. 7 Cardiac dysfunction among patients with dilated cardiomypathy secondary to hypothyroidism can be reversed with thyroid hormone replacement therapy. 3,6 Although hypothyroidism alone is an uncommon cause of dilated cardiomyopathy, clinicians should perform thyroid function tests in patients with un explained dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Karolina Zawadzka published a review in 2021, Radosław Dziedzic [4] showed that not only the local bioavailability of myocardial thyroid hormones could be decreased due to altered expression of desiodase, but practically all genes involved in thyroid hormone biosynthesis are expressed in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Le mécanisme exact d'apparition de la myocardiopathie dilatée chez la patientèle atteinte d'hypothyroïdie reste à déterminer. Outre l'action connue des hormones thyroïdiennes sur le coeur, passant par des effets génomiques et non génomiques, des études récentes ont permis de constater des variations de l'expression génique associées à la biosynthèse ou à la diminution de la biodisponibilité de ces hormones dans les tissus de la patientèle atteinte de myocardiopathie dilatée 7 . La dysfonction cardiaque de la patientèle atteinte de myocardiopathie dilatée secondaire à une hypothyroïdie peut être réversible avec une hormonothérapie thyroïdienne substitutive 3,6 .…”
Section: Discussionunclassified